205k views
1 vote
Consider the sequence of steps to solve the equation: 5(x - 3) = 7x 2 step 5

User Arjabbar
by
5.6k points

2 Answers

2 votes

5(x-3) = 14 (you have to simplify 7 x 2 = 14)

x-3 = 14/5 (divide both sides by 5)

x= 14/5 + 3 (add 3 to both sides)

x= 29/5 (simplify)

User JoeyD
by
5.5k points
6 votes

Answer:Solving 5(x - 3) = 7x/2

Step 1 ⇒ 10(x - 3) = 7x

Step 2 ⇒ 10x - 30 = 7x

Step 3 ⇒ 3x - 30 = 0 . . . . . . addition (or subtraction) property of equality

Step 4 ⇒ 3x = 30

Step 5 ⇒ x = 10

User Selim Ok
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.